Biokinetics and biotransformation of paralytic shellfish toxins in different tissues of Yesso scallops, Patinopecten yessoensis. (December 2020) - Liu, Yang; Kong, Fan-Zhou; Xun, Xiao-Gang; Dai, Li; Geng, Hui-Xia; Hu, Xiao-Li; Yu, Ren-Cheng; Bao, Zhen-Min; Zhou, Ming-Jiang
Abstract: Paralytic shellfish toxins (PSTs) are a group of natural toxic substances often found in marine bivalves. Accumulation, anatomical distribution, biotransformation and depuration of PSTs in different tissues of bivalves, however, are still not very well understood. In this study, we investigated biokinetics and biotransformation of PSTs in six different tissues, namely gill, mantle, gonad, adductor muscle, kidney, and digestive gland, in Yesso scallops Patinopecten yessoensis exposed to a toxic strain of dinoflagellate Alexandrium pacificum . High daily accumulation rate (DAR) was recorded at the beginning stage of the experiment. Most of the PSTs in toxic algae ingested by scallops were retained and the toxicity level of PSTs in scallops exceeded the regulatory limit within 5 days. At the late stage of the experiment, however, DAR decreased obviously due to the removal of PSTs. Fitting results of the biokinetics model indicated that the amount of PSTs transferred from digestive gland to mantle, adductor muscle, gonad, kidney, and gill in a decreasing order, and adductor muscle, kidney, and gonad had higher removal rate than gill and mantle. Toxin profile in digestive gland was dominated by N- sulfocarbamoyl toxins 1/2 (C1/2), closely resembled that of the toxic algae. In contrast, toxin components in kidney were dominated by high-potency neosaxitoxin (NEO) and saxitoxin (STX), suggesting that the kidney be a major organ for transformation of PSTs. Graphical abstract: Image 1 Highlights: Kinetics and transformation of paralytic shellfish toxins in scallops were studied. Daily accumulation rate was high during the first 5 days and then decreased rapidly. Digestive gland retained most toxins and had the highest concentration of toxins. Kidney contained high-potency toxin components and had the highest toxicity level. Kidney may serve as a major organ for biotransformation of toxins in scallops.